2012
DOI: 10.1161/cir.0b013e3182507bec
|View full text |Cite
|
Sign up to set email alerts
|

ACCF/AHA/AMA-PCPI 2011 Performance Measures for Adults With Heart Failure

Abstract: . Expert peer review of AHA Scientific Statements is conducted by the AHA Office of Science Operations. For more on AHA statements and guidelines development, visit http://my.americanheart.org/statements and select the "Policies and Development" link.Permissions: Multiple copies, modification, alteration, enhancement, and/or distribution of this document are not permitted without the express permission of the American Heart Association. http://www.heart.org/HEARTORG/General/Copyright-Permission-Guidelines_UCM_… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(65 citation statements)
references
References 29 publications
1
63
1
Order By: Relevance
“…Although advantageous from efficiency and cost perspectives, most of the other reasons listed for incomplete decongestion represented situations in which the physical examination did not accurately reflect the patient's optimal volume status. Current guidelines also recommend the initiation or continuation and uptitration of neurohormonal doses toward target, when possible, by the time of hospital discharge for patients with HFrEF 30. In this study, we found lower rates of adherence to guidelines regarding use of β‐blockers (58%) and ACEi/ARB (53%) at discharge than have been observed in prior studies 31, 32.…”
Section: Discussioncontrasting
confidence: 52%
“…Although advantageous from efficiency and cost perspectives, most of the other reasons listed for incomplete decongestion represented situations in which the physical examination did not accurately reflect the patient's optimal volume status. Current guidelines also recommend the initiation or continuation and uptitration of neurohormonal doses toward target, when possible, by the time of hospital discharge for patients with HFrEF 30. In this study, we found lower rates of adherence to guidelines regarding use of β‐blockers (58%) and ACEi/ARB (53%) at discharge than have been observed in prior studies 31, 32.…”
Section: Discussioncontrasting
confidence: 52%
“…This rate, however, is consistent with a prior GWTG‐HF study 20. The high rates of ACEi/ARB prescription in this study may reflect the impact of including ACEi/ARB as a performance measure9, 21 and the results of quality improvement efforts made during this time (2005‐2013). The percentage may also be high due to selection bias, and hospitals that choose to participate in GWTG may be different from those that do not.…”
Section: Discussionsupporting
confidence: 86%
“…The American College of Cardiology (ACC)/American Heart Association (AHA) clinical guidelines make it a Class I, Level A recommendation to use ACEi/ARB therapy in patients with HFrEF both to “prevent symptomatic heart failure” and to “reduce morbidity and mortality.”8 In addition, the ACC/AHA HF Performance Measures recommend ACEi/ARB for outpatients with HFrEF and ACEi/ARB therapy at the time of hospital discharge for inpatients with HFrEF 9. These clinical guidelines and quality metrics, along with their associated incentives, have led to significant improvements in the rates of ACEi/ARB use over time.…”
Section: Introductionmentioning
confidence: 99%
“…Delivery of comprehensive patient education prior to discharge is recommended in all major HF guidelines [13,14] and is a quality performance measure for hospitals [15,16]. Required topics are activity, diet, understanding medications and follow-up care, daily weight monitoring, and what to do with worsening signs or symptoms of HF.…”
Section: Inpatient-based Strategiesmentioning
confidence: 99%